2003
DOI: 10.1128/jb.185.4.1218-1228.2003
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Functional Activity ofChlamydiaMurA, a UDP-N-Acetylglucosamine Enolpyruvyl Transferase Involved in Peptidoglycan Synthesis and Fosfomycin Resistance

Abstract: Organisms of Chlamydia spp. are obligate intracellular, gram-negative bacteria with a dimorphic developmental cycle that takes place entirely within a membrane-bound vacuole termed an inclusion. The chlamydial anomaly refers to the fact that cell wall-active antibiotics inhibit Chlamydia growth and peptidoglycan (PG) synthesis genes are present in the genome, yet there is no biochemical evidence for synthesis of PG. In this work, we undertook a genetics-based approach to reevaluate the chlamydial anomaly by ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
97
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(101 citation statements)
references
References 37 publications
(36 reference statements)
3
97
0
1
Order By: Relevance
“…The expected 20,21) . The sequence analysis demonstrated that there is no replacement in the active site of S. mutans MurA.…”
Section: Discussionmentioning
confidence: 99%
“…The expected 20,21) . The sequence analysis demonstrated that there is no replacement in the active site of S. mutans MurA.…”
Section: Discussionmentioning
confidence: 99%
“…[85][86][87] Once inside the cell, fosfomycin acts as an analog of phosphoenolpyruvate and inhibits enolpyruvyl transferase (also known as MurA), a cytoplasmic enzyme that allows the first step of synthesis of N-acetylmuramic acid. 86,[88][89][90][91] Because N-acetylmuramic acid is a major component of glycan strands in the cell wall, fosfomycin blocks cell wall synthesis with a lethal effect. 86,92,93 …”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…The resistance of enolpyruvyl transferase to inactivation by fosfomycin was demonstrated in Mycobacterium tuberculosis, 94 Vibrio fisheri, 95 and Chlamydia trachomatis. 91 In susceptible organisms, several mutations in murA demonstrate a lower affinity of its product to phosphoenolpyruvate and may lead to fosfomycin resistance 96-98 associated with a lower rate of peptidoglycan synthesis. 98 However, resistance to fosfomycin due to overexpression of enolpyruvyl transferase has been also observed.…”
Section: Mechanisms Of Resistancementioning
confidence: 99%
“…Furthermore, a recombinant E. coli strain where the MurA gene was replaced with the C. trachomatis MurA gene was resistance to fosfomycin, 12 suggesting that the aspartate substitution is highly important to fosfomycin resistance. The structure or kinetic properties of MurAs from C. trachomatis or M. tuberculosis have not yet been reported due to the difficulties associated with expressing recombinant proteins, even though inhibitors of these MurAs would be valuable for the development of antibiotics against C. trachomatis or M. tuberculosis.…”
Section: 1213mentioning
confidence: 99%
“…12,13 The fosfomysin resistance of these bacteria is probably due to the resistance of MurA, since MurA of M. tuberculosis or C. trachomatis contains an aspartate residue at the active site loop instead of cysteine. Therefore, we tested whether C117D substitution affected the sensitivity of Hi MurA to fosfomycin.…”
mentioning
confidence: 99%